Electronic reminding technology for cognitive impairment. - Mason, Sarah; Craig, David; O'Neill, Sonia; Donnelly, Mark; Nugent, Chris (British Journal of Nursing, 2012)
Demographic changes highlight the need to address disabilities associated with the costly morbidities of old age, such as dementia. Memory impairment associated with dementia represents a significant challenge for many older people. Difficulties occur in carrying out activities in their entirety or in commencing them at all. Technology has the potential to help individuals overcome the barriers created by cognitive disability in terms of performing activities of daily living and therefore help to maintain independence and enhance quality of life (Czaja, 2005). This literature review examines the current reported research, which employs electronic reminding technology to support individuals with cognitive impairment. These devices range from everyday technologies, such as phones, to sophisticated interactive devices with specifically designed software. A summary of the current evidence base is presented and recommendations for future practice are made.